Answer:
x = 2
y = 4
Explanation:
From the question given above, the following data were obtained:
y = 2x
x = – y + 6
The solutions to the equation can be obtained as follow:
y = 2x ...... (1)
x = – y + 6 ......(2)
Substitute the value of y in equation (1) into equation (2)
x = – y + 6
y = 2x
x = – 2x + 6
Collect like terms
x + 2x = 6
3x = 6
Divide both side by 3
x = 6/3
x = 2
Substitute the value of x into equation (1) to obtain y.
y = 2x
x = 2
y = 2(2)
y = 4
Thus, the solutions to the equations are:
x = 2
y = 4